2015
DOI: 10.1111/ijfs.12771
|View full text |Cite
|
Sign up to set email alerts
|

Separation of angiotensin I‐converting enzyme inhibitory peptides from bovine connective tissue and their stability towards temperature, pH and digestive enzymes

Abstract: Bovine collagen was isolated from connective tissue, a by-product in the meat processing industry and characterised by SDS-PAGE. Alcalase and papain were employed to generate collagen hydrolysates with different degree of hydrolysis (DH). In vitro angiotensin I-converting enzyme (ACE) inhibitory activities were evaluated and the two most potent hydrolysates from each enzyme were separated by two-step purification. Both alcalase-catalysed and papain-catalysed hydrolysates exhibited strong ACE inhibitory capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 51 publications
1
22
0
1
Order By: Relevance
“…The impact of pH (2.0-10.0) on the ACEIA of collagen hydrolysates afforded a significant reduction of ACEIA at strong alkaline conditions (pH 10.0). Similarly, in agreement with our research, collagen peptides exhibited good resistance against the acidic and weak alkaline conditions and heat treatment (Fu et al 2015).…”
supporting
confidence: 92%
See 2 more Smart Citations
“…The impact of pH (2.0-10.0) on the ACEIA of collagen hydrolysates afforded a significant reduction of ACEIA at strong alkaline conditions (pH 10.0). Similarly, in agreement with our research, collagen peptides exhibited good resistance against the acidic and weak alkaline conditions and heat treatment (Fu et al 2015).…”
supporting
confidence: 92%
“…Thus, the collagen peptides may endure digestion considerably through the gastrointestinal tract or they may be partially degraded into smaller peptides whilst retaining their activity. Collagen peptides display potent ACEIA after an in vitro digestion, possibly due to posttranslational hydroxylation of proline in collagen (Fu et al 2015).…”
Section: Stability Of Bioactivity Of Hydrolysates On An In Vitro Gastmentioning
confidence: 99%
See 1 more Smart Citation
“…Yak (Bos grunniens) is a kind of cattle which can survive on Tibetan plateau due to their tenacious vitality and adaption to cold climates and low oxygen pressure. In previous study, bovine collagen showed excellent ACE inhibitory activity with IC 50 of 3.95 and 7.29 lg mL 21 (Fu et al 2015). As yak live in a pollution-free environment, and mainly grow naturally without manual feed, it is safer and healthier to obtain valuable products such as meat, skin, milk and horn from them.…”
Section: Introductionmentioning
confidence: 94%
“…Although the hydrolysates and the control (captopril, an antihypertensive drug) were fed at different concentrations, both showed a similar trend in lowering the SBP of SHRs. Fu, Young, Dalsgaard, and Therkildsen () recently generated enzymatic hydrolysates from bovine connective tissue using Alcalase and papain and different degrees of hydrolysis. The two most potent hydrolysates showed IC 50 values of 0.17 and 0.35 mg/mL for Alcalase and papain, respectively.…”
Section: Biologically Active Peptides Generated From Bovine and Porcimentioning
confidence: 99%